Factors associated with disease progression in dogs with presumed preclinical degenerative mitral valve disease attending primary care veterinary practices in the United Kingdom. (18th December 2018) - Mattin, Madeleine J.; Brodbelt, David C.; Church, David B.; Boswood, Adrian
Abstract : Background: Factors associated with disease progression in dogs with preclinical (stage B) degenerative mitral valve disease (DMVD) have not been evaluated previously in primary care veterinary practice. Objectives: To evaluate whether plasma cardiac biomarkers, clinical signs, and physical examination findings are associated with clinical progression (reaching the composite endpoint of initiation of treatment with a potent diuretic or cardiac death) in dogs presumed to have stage B DMVD. Animals: Six‐hundred and eighty‐four dogs diagnosed with DMVD recruited from 73 primary care practices in the United Kingdom. Dogs were not receiving potent diuretics at recruitment. Methods: Prospective cohort study design. Primary care veterinarians recorded the presence or absence of clinical signs and physical examination findings. Baseline plasma N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) and cardiac troponin I were measured. Cox regression models measured associations between risk factor variables and clinical progression. Flexible parametric models generated predicted probabilities of reaching the composite endpoint for dogs with different combinations of prognostic risk factor variables. Results: Plasma NT‐proBNP, heart rate, heart murmur intensity, presence of a cough, being a Cavalier King Charles Spaniel, and being prescribed pimobendan were associated with clinical progression to initiation of treatment with a potent diuretic or cardiac‐related death. Conclusions and Clinical Importance: Dogs with stage B DMVD identified as having a high risk of disease progression might benefit from more frequent monitoring or further diagnostic evaluation. The prognostic factors identified could facilitate risk stratification of dogs presenting with preclinical DMVD.